Development and preliminary evaluation of tablet computer-based decision aid for patients participating in cancer clinical trials - Hiroko Okada (Elsevier, 2021)
Objectives: Patients often consent to participate in cancer clinical trials despite misunderstanding the trial content. We developed a tablet-based clinical trial decision aid and tested its use with the usual discussion at the time of clinical trial registration. Methods: Participants were individuals considering participating in a breast cancer clinical trial. The control participated in usual discussions; the intervention group participated in discussion using the decision aid. Pre- and post-discussion, we investigated knowledge, decision-making conflict, and discussion length. Results: We enrolled 54 patients, 27 in the control group and 27 in the intervention group. Post-discussion clinical trial knowledge was significantly higher in the intervention group than in the control group (p = 0.003). No significant difference was found in decisional conflict, but the intervention group tended to have lower post-discussion conflict than the control group. There was no between-group difference in the length of discussions with physicians and clinical research coordinators. Conclusion: For women considering participation in cancer clinical trials, a tablet-based decision aid may promote clinical trial understanding without increasing discussion length or patient burden. This pre-learning decision aid incorporating a quiz and bidirectional question prompt lists may improve participants’ understanding of clinical trials.